Test of VAK Learning Style on Student Learning Outcomes Using Single-Test Reliability - Suryono, Wiwid; Setiawan, Ariyono; Suprapto, Yuyun; Kustori, Kustori (Technium Social Sciences Journal, 2021)
This study aims to examine the effect of the VAK Learning Style (Visual, Auditory, and Kinesthetic) on learning Basic Physics Techniques using a digital simulation model using the Single-Test Reliability application on the learning outcomes of cadets at the Aviation Polytechnic of Surabaya. The research method is descriptive quantitative with a quasi-experimental design, namely research that is intended to determine whether there is a consequence of something imposed on the subject under investigation. The participants in this study cadets of the Airport Electrical Engineering Study Program at the Aviation Polytechnic of Surabaya. The data generated is the tendency of cadets' learning styles in doing exercises and final tests using the Single-Test Reliability application on learning outcomes. The data obtained shows that cadets who have a tendency for visual learning styles get higher exercise and final test scores than cadets with auditory and kinestatic learning styles. The use of the Single-Test Reliability application increased learning outcomes from the initial class average of 64.2 become 81, with the highest average score obtained by cadets with visual learning styles.